Benin : 2022 Article IV Consultation and Requests for an Extended Arrangement under the Extended Fund Facility and an Arrangement under the Extended Credit Facility-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for Benin. (IMF Staff Country Reports; Country Report ;, 2022)
The Beninese government embarked, five years ago, on an ambitious reform agenda ("Revealing Benin") to revive the economy and improve the wellbeing of the people. Economic activity accelerated prior to the COVID-19 pandemic, with sound macroeconomic management and enhanced budget transparency culminating in access to international capital markets in 2019 and issuance of the first-ever SDG bond by an African sovereign last year. However, today, Benin faces significant headwinds from a deteriorating security situation at its northern borders, pandemic-induced scars, and higher cost of living amidst the war in Ukraine, which could impact hard-won macroeconomic gains and cause hardship. The authorities have requested a Fund-supported program to meet pressing financing needs, preserve macroeconomic stability, and anchor the country's National Development Plan centered on achieving the Sustainable Development Goals (SDGs).